Die Getrennt- und Zusammenschreibung von Komposita in frnhd. Hexenverhörprotokollen - Lisa Dücker (Zeitschrift für Wortbildung)
This paper investigates the spelling of compound nouns in a corpus comprised of Early New High German protocols of witch trials from the 16th and 17th century. Previous studies on the spelling of compound nouns in printed texts have found that scribes increasingly write compound nouns as one word during the 16th century. However, this paper will show that there is still much variation in handwritten texts from that time. The study focusses on identifying factors that lead scribes to write compound nouns either as one word or two, such as linking elements and the use of upper case letters. I will argue that while there is more variation in the spelling of compound nouns in the handwritten corpus than in printed texts, there still is a strong tendency to line up the boundaries of the graphemic and syntactic words.